P084 Student perspectives on rheumatology teaching in undergraduate medical training in the UK in 2021. (23rd April 2022) - Hanna, David; Wakefield, Sophia; Southam, Daisy; Andrew, Donna; Wakefield, Richard; Coady, David
Abstract: Background/Aims: In 2000, a survey of medical educators was published exploring undergraduate rheumatology training across medical schools in the UK. This has recently been repeated. However, neither have surveyed the opinions of the medical students themselves - arguably the most important stakeholders. To evaluate how students perceive their rheumatology training, understand how they best learn and to explore how they engage with rheumatology on clinical placements, especially in the context of the COVID-19 pandemic. Methods: An online survey was emailed to students from medical schools across the UK. "Snowball sampling" was used, where individual social contacts were used to create a network of medical students from each of the 37 medical schools across the UK through social media such as SMS, WhatsApp, Facebook messenger, and Instagram. Students were asked similar questions as those in the teacher survey; however, emphasis was placed on their perspective of teaching methods and their clinical placements. Results: 30 completed surveys were returned (81%) but not all questions were answered. Of those, 27/28 (97%) identified some sort of MSK teaching, in contrast to only 16/28 (57%) being able to identify specific rheumatology teaching. This was delivered in diverse ways; 42% (10/24) learnt it in a block, while 38% (9/24) had this teaching spread out over a longer period of time. Teaching was quite varied amongst the schools. On average 9 days were spent learning rheumatology. The most commonly used methods were lectures, small-group teaching, and online tutorials. This contrasts with what students felt was most effective, which were small-group sessions, expert patient teaching and teaching OSCE's. It was noted that medical education and placements had been very different over the previous 18 months with a 41% decrease in patient contact during COVID-19 pandemic. Most students found rheumatology as a difficult field to approach. 66% (14/21) were not aware of any specific rheumatology SSCs or personal excellence pathways. 86% (19/22) stated there was limited-to-no promotion of rheumatology as a specialty in their medical school, and 87% (26/30) weren't aware of VA, ARUK, or BSR resources to assist in their rheumatology education. Conclusion: This is the first survey to evaluate the views of medical undergraduates on their rheumatology teaching in the UK. It is intended that this data will be triangulated with the medical teacher survey. The findings highlight that what students would prefer in terms of teaching i.e. face to face teaching with patients, is not what is currently being delivered (mainly lectures, on-line tutorials). Of some concern there appeared to be a general lack awareness of available online resources, especially from VA and BSR, suggesting marketing of these may not be effective. Disclosure: D. Hanna: None. S. Wakefield: None. D. Southam: None. D. Andrew: None. R. Wakefield: None. D. Coady: None.